MicroRNAs associated with chronic kidney disease in the general population and high-risk subgroups: protocol for a systematic review and meta-analysis. Issue 2 (16th February 2022) - Motshwari, Dipuo Dephney; Matshazi, Don Makwakiwe; Erasmus, Rajiv; Kengne, AP; Matsha, Tandi E; George, Cindy
Abstract : Introduction: Chronic kidney disease (CKD) is a significant health and economic burden, owing to its ever-increasing global prevalence. Due to the limitations in the current diagnostic methods, CKD is frequently diagnosed at advanced stages, where there is an increased risk of cardiovascular complications and end-stage kidney disease. As such, there has been considerable interest in microRNAs (miRNAs) as potential markers for CKD detection. This review seeks to identify all miRNAs associated with CKD and/or markers of kidney function or kidney damage in the general population and high-risk subgroups, and explore their expression profiles in these populations. Methods and analysis: A systematic search of published literature will be conducted for observational studies that report on miRNAs associated with CKD or kidney function or kidney damage markers (serum creatinine and cystatin C, estimated glomerular filtration rate and urinary albumin excretion) in adult humans. The electronic database search will be restricted to English and French publications up to 31 October 2021. Two investigators will independently screen and identify studies for inclusion, as well as extract data from eligible studies. Risk-of-bias and methodological quality will be assessed by the Newcastle-Ottawa Quality Assessment Scale for observational studies and Grading of Recommendations Assessment, Development and Evaluation tools. Appropriate meta-analytic techniques will be used to pool estimates from studies with similar miRNAs, overall and by major characteristics, including by country or region, sample size, gender and risk-of-bias score. Heterogeneity of the estimates across studies will be quantified and publication bias investigated. This protocol is reported according to Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols 2015 guidelines. Ethics and dissemination: This study design does not require formal ethical clearance and findings will be published in a peer-reviewed journal. Conclusion: This review will provide the expression pattern of miRNAs associated with CKD. This will allow for further research into the identified miRNAs, which could later be used as biomarkers for prediction and early detection of CKD, monitoring of disease progression to advanced stages and as potential therapeutic targets. PROSPERO registration number: CRD42021270028.